OP0052 COMPARISON OF PATIENTS WITH PSORIATIC ARTHRITIS (PSA) AND INVESTIGATOR-DEFINED AXIAL PSA TO PATIENTS WITH PSA AND ELEVATED PATIENT-REPORTED SPINE PAIN: FINDINGS FROM THE CORRONA PSORIATIC ARTHRITIS/SPONDYLOARTHRITIS (PSA/SPA) REGISTRY. (2nd June 2020) - Ogdie, A.; Blachley, T.; Glynn, M.; Rebello, S.; Dube, B.; Mclean, R.; Hur, P.; Mease, P. J.
Abstract : Background: Efforts are underway by GRAPPA and ASAS to define axial disease in psoriatic arthritis (axPsA). 1 AxPsA is typically diagnosed based on clinical evaluation and judgement, imaging, and patient-defined axial symptoms. In the MAXIMISE trial, part of the inclusion criteria for axPsA required patients to have a BASDAI ≥ 4 and patient-reported spine pain ≥ 40 in addition to clinician judgement. 2 Objectives: To compare characteristics of patients with PsA and investigator-identified axPsA to patients with PsA with BASDAI ≥ 4 and patient-reported spine pain ≥ 40. Methods: Adult patients with PsA enrolled in the registry from March 2013–December 2019 were included. Investigators identified the subset of patients with axPsA based on clinical assessments, imaging, and laboratory workup. All patients completed a BASDAI questionnaire and spine pain VAS. Patients with investigator-identified axPsA were compared with those who had BASDAI ≥ 4 and spine pain VAS ≥ 40 (elevated spine symptoms; non-mutually exclusive groups). Presence of other manifestations at enrollment was also evaluated: enthesitis (SPARCC enthesitis count > 0), dactylitis (dactylitis count > 0), peripheral arthritis (PA; tender and/or swollen joint count > 0), nail psoriasis (VAS > 0), skin psoriasis (affected body surface area > 0%). The prevalence of investigator-defined axPsA and elevated spine symptoms, alone and with other manifestations, was summarized for all patients and those who initiated biologics at enrollment using frequency counts and percentages. Results: Of 3393 patients with PsA, 391 (11.5%) had investigator-defined axPsA and 863 (25.4%) had elevated spine symptoms (Figure 1 A ); 127 (3.7%) patients met both criteria. In the total population with PsA, 2982 patients had ≥ 1 PsA manifestation when axPsA was investigator defined, of whom 2235 (74.9%) had multiple manifestations. Among those with ≥ 1 manifestation, the most common presentations were PA + skin (14.6%), skin (13.1%), and PA + nail + skin (11.3%). When using the criteria for elevated spine symptoms, 2996 patients had ≥ 1 PsA manifestation, of whom 2299 (76.7%) had multiple manifestations. Among those with ≥ 1 manifestation, the most common presentations were skin (12.3%), PA + skin (11.2%), and PA + nail + skin (8.8%). Of 769 patients who initiated a biologic at enrollment, 109 (14.2%) had investigator-defined axPsA and 270 (35.1%) had elevated spine symptoms (Figure 2 A ). Among all biologic initiators with PsA, 733 had ≥ 1 PsA manifestation when axPsA was investigator defined, of whom 630 (85.9%) had multiple manifestations; the most common presentations were PA + skin (16.2%), PA + skin + nail (12.8%), and enthesitis + PA + nail + skin (7.8%). When using the criteria for elevated spine symptoms, 732 biologic initiators had ≥ 1 disease manifestation, of whom 650 (88.8%) had multiple manifestations; the most common presentations were PA + skin (11.7%), PA + skin + nail (8.5%), and PA + axPsA + skin (6.3%). The prevalence of skin, PA, and dactylitis was higher in those with elevated spine symptoms vs investigator-defined axPsA, whereas the prevalence of enthesitis was higher in those with investigator-defined axPsA (Figure 1 B and 2B ). Conclusion: In the Corrona PsA/SpA Registry, there was a higher number of patients with elevated spine symptoms than with investigator-defined axPsA; these patients also had more coexisting manifestations. Although they may have had other reasons for back pain (ie, degenerative spine disease or central sensitization), it is possible that axPsA could be present in some and this warrants further evaluation. References: [1]Goel N, et al. J Rheumatol . 2019;95(Suppl):54-7. [2]Baraliakos X, et al. Ann Rheum Dis . 2019;78:195-6. Disclosure of Interests: Alexis Ogdie Grant/research support from: Pfizer to Penn, Novartis to Penn, Amgen to Forward/NDB, Consultant of: Abbvie, Amgen, Bristol-Myers Squibb, Celgene, Corrona, Janssen, Eli Lilly, Novartis, Pfizer, Taylor Blachley Employee of: Corrona, LLC, Meghan Glynn Shareholder of: Corrona, LLC – shareholder, Grant/research support from: Pfizer – grant/research support, Employee of: Corrona, LLC – employment, Sabrina Rebello Employee of: Corrona, LLC, Blessing Dube Employee of: Corrona, LLC, Robert McLean Employee of: Corrona, LLC, Peter Hur Employee of: Novartis Pharmaceuticals Corporation, Philip J Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – grant/research support, Consultant of: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – consultant, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Eli Lilly, Genentech, Janssen, Pfizer, UCB – speakers bureau